The Traditional phyto-recipes used to cure various ailments by the local people of Shishi Koh valley, Chitral, Pakistan - Wali, Sher; Jan, Hammad Ahmad; Haq, Shiekh Marifatul; Yaqoob, Umer; Bussmann, Rainer W; Rahim, Fazli (Ethnobotany Research and Applications, 2021)
Background: Medicinal plants are used to cure a variety of ailments since ancient times. In last few decades an increase in interest in the use of medicinal plants is noted for discovering novel medicines and treatments to fulfill the needs of the increasing population. This study was aimed to document phyto-recipes used by the indigenous communities of Shishi Koh Valley, Chitral. Methods: The data was collected during 2019-2020 through interviews (N=125) using semi-structured and close-ended questionnaires. The data obtained was quantitatively analyzed through the family importance value (FIV), familiarity index (FI) informant consensus factor (ICF) and consensus index in percent (CI%). Results: During the field work we have collected 48 medicinal plant species belonging to 29 families. According to the result herbs are the most dominant life form (56%), followed by trees (29%). Leaves were the most frequent plant parts used in phyto-recipes. The 89 indigenous recipes were reported to cure different diseases. Asteraceae family was dominant with the highest family importance value (FIV = 0.616), whereas Rumex hastatus D. Don depicted maximum familiarity index (FI = 0.456). A decoction was the common mode of medicines preparation. The digestive disorders have the highest value of informant consensus factor (ICF = 0.93) and the least value of ICF was obtained for Skin problems (0.53). Conclusion: The present study revealed the importance of the flora of this unexplored area. We recommended that in future the plants like Rumex hastatus D. Don having high FI should be studied for phyto-chemically, and pharmacologically to discover new drugs. Keywords: Herbal Recipes; Medicinal Plants; Ethnomedicines; Shishi Koh Chitral; Pakistan